The empathic healer : an endangered species? - Bennett, M. J. (Michael Julian) (Practical resources for the mental health professional., 2001)
Empathy has long been regarded as central to the art of medicine and especially to the practice of psychotherapy. The ability of a therapist to appreciate the patient's state of mind and frame of reference is the foundation of a therapeutic alliance and key to the process of healing. However, these subjective aspects of practice are rendered suspect by today's emphasis on objectivity: formal diagnosis, with biological treatments, and standardized methodologies that appear to be aimed more at disease than at the person who suffers from it. Pressured by the practice climate and by the advances of science, practitioners have become treatment specialists and the empathic healer has become an endangered species. In this book, the author establishes a new foundation for the use and value of clinical empathy that is based on a distinction between treatment and healing and a model for using psychotherapy as a component of an organized system of care: focused, attuned to the patient's presenting motive, and consistent with our understanding of the relationship between mind and brain. Practicing mental health professionals and students find the rationale for assessment and treatment planning in The Empathic Healer an invaluable aide as they seek to adapt to the marvelous discoveries about how the brain shapes and recovers from mental disorder, and how an empathic environment fosters recovery and healing within and beyond the treatment setting. Key Features * Establishes the historical roots of the concept of clinical empathy and its relationship to healing * Elaborates the ideological and environmental factors that enhance or interfere with empathy * Explores the biological importance of empathy as a feature of the normal human brain * Argues for the integration of mind and brain in a new dualism * Presents a vision of psychotherapy as an important component of an organized system of care * Differentiates between the treating and healing functions, and suggests how each relies on empathy * Suggests how an endangered species may be preserved in the present technological era.